Interleukin-10 Attenuates Liver Fibrosis Exacerbated by Thermoneutrality - Nga, Ha Thi; Moon, Ji Sun; Tian, Jingwen; Lee, Ho Yeop; Kim, Seok-Hwan; Lee, Young-Sun; Jeon, Jae-Han; Yi, Hyon-Seung (Frontiers in Medicine, 2021)
Background Crosstalk between brown adipose tissue (BAT) and the liver is receiving increasing attention. This study investigated the effect of BAT dysfunction by thermoneutral (TN) housing on liver fibrosis in mice and examined the effect of secreted factors from brown adipocytes on the activation of hepatic stellate cells (HSCs). Methods The carbon tetrachloride (CCl4)-induced liver fibrosis mouse model was used to evaluate fibrotic changes in the livers of mice housed under standard and TN conditions. The effect of BAT on the activation of HSCs was examined using cultured cells treated with conditioned media from brown adipocytes. Results Under TN conditions, mice with CCl4-induced liver fibrosis exhibited increased liver injury, collagen deposition, and alpha smooth muscle actin (α-SMA) expression in the liver compared with mice maintained at room temperature. The numbers of liver-infiltrating immune cells and T cells producing IL-17A and IFN-γ were also significantly increased in the livers of mice housed under TN conditions. Treatment of HSCs with conditioned media from brown adipocytes markedly attenuated HSC activation, as shown by down-regulated α-SMA expression at day 4, day 7 and day 10 of culture. At thermoneutrality, with CCl4 administration, IL-10-deficient mice exhibited more severe liver fibrosis than wild-type mice. Interestingly, conditioned media from IL-10-deficient brown adipocytes could up-regulate the expression of α-SMA and induce HSCs activation. Conclusions BAT inactivation by thermoneutrality contributes to the activation of pro-inflammatory and pro-fibrotic pathways in mice with CCl4-induced liver fibrosis. Normal brown adipocytes secreted factors that impair the activation of HSCs, while this protective effect was lost in IL-10-deficient brown adipocytes. Thus, the BAT–liver axis may serve as a potential therapeutic target for liver fibrosis, and IL-10 may be a key factor regulating the activation of HSCs by BAT.